2022
DOI: 10.1021/acs.jmedchem.1c01598
|View full text |Cite
|
Sign up to set email alerts
|

Thieno[2,3-d]pyrimidine-2,4(1H,3H)-dione Derivative Inhibits d-Dopachrome Tautomerase Activity and Suppresses the Proliferation of Non-Small Cell Lung Cancer Cells

Abstract: The homologous cytokines macrophage migration inhibitory factor (MIF) and d -dopachrome tautomerase ( d -DT or MIF2) play key roles in cancers. Molecules binding to the MIF tautomerase active site interfere with its biological activity. In contrast, the lack of potent MIF2 inhibitors hinders the exploration of MIF2 as a drug target. In this work, screening of a focused compound collection enabled the identification of a MIF2 tautomerase inhibitor R110. Subsequent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Previous studies have shown that D-DT is less active that MIF. 29,31 This conclusion is also confirmed All residues have chemical shift perturbations larger than 1SD in at least one condition except T112, which is shown as an example of differential broadening. The largest differences in chemical shift perturbation between 4-HPP from Chemodex and TCI are italicized.…”
Section: Nmr Binding Studies Between Mif and 4-hpp Samples Show Diffe...supporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have shown that D-DT is less active that MIF. 29,31 This conclusion is also confirmed All residues have chemical shift perturbations larger than 1SD in at least one condition except T112, which is shown as an example of differential broadening. The largest differences in chemical shift perturbation between 4-HPP from Chemodex and TCI are italicized.…”
Section: Nmr Binding Studies Between Mif and 4-hpp Samples Show Diffe...supporting
confidence: 62%
“…The low amino acid identity has a direct impact on the composition, hydrophobicity, and ligand selectivity of each active site . Thus far, D-DT has only three reversible inhibitors, all of which were discovered via the tautomerization assay of 4-HPP. ,, In contrast to MIF and D-DT, HPPD is a homodimeric enzyme that catalyzes dioxygenation of 4-HPP in the second step of tyrosine catabolism. Incorporation of molecular oxygen in 4-HPP yields homogentisate (HGA) and the reaction requires inorganic iron as a cofactor.…”
mentioning
confidence: 99%
“…Whereas CPSI-1306 was a preclinical candidate compound with some effort generated toward optimizing pharmacology, 4-IPP is not an optimized compound. As noted previously, at the time these studies were performed, 4-IPP was the only MIF2 inhibitor available, although other compounds have very recently been demonstrated to functionally block MIF2 [21]. More importantly, when MIF1 À/À animals were treated with 4-IPP, we saw a major reduction in tumor stage and a partial replication of a previously observed phenotype, so that these animals did not proceed to MIBC to the same degree.…”
supporting
confidence: 65%
“…Comprehensive validation of these data would require a Ddt À/À animal or an inhibitor with well-defined pharmacology and a strong preference for MIF2 over MIF1. Novel MIF2 inhibitor chemotypes have recently been identified but remain poorly validated with regard to cellular penetration, efficacy, and pharmacokinetics [20,21]. Although we believe that these data support the idea that MIF2 is involved in BCa tumorigenesis, future studies using validated versions of more specific compounds or animals deficient in either MIF2 or in both MIF1 and MIF2 to validate these results are warranted, particularly in the context of cell-specific knockout.…”
mentioning
confidence: 78%
See 1 more Smart Citation